2001
DOI: 10.1046/j.1423-0410.2001.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviour among blood donors who give blood in order to be tested for the human immunodeficiency virus

Abstract: The proportion who donated blood in order to be HIV tested was higher than expected, but the majority of the group did not have any identifiable HIV risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 1 publication
(1 reference statement)
4
30
0
3
Order By: Relevance
“…The estimated number of Y alleles gave concordant results with the number of males reported by two surveys of people donating blood to the Oslo blood bank in 1998 and 2000 [9,10], the same year these samples were collected ( Table 1). …”
Section: Discussionsupporting
confidence: 78%
“…The estimated number of Y alleles gave concordant results with the number of males reported by two surveys of people donating blood to the Oslo blood bank in 1998 and 2000 [9,10], the same year these samples were collected ( Table 1). …”
Section: Discussionsupporting
confidence: 78%
“…The main underlying reason for this problem is that testing for HIV is free of charge and fast at blood centers and people wish to avoid the social stigmatization of specifically being tested for HIV. 3,4 Confidential self-exclusion (CSE) systems have been designed for this type of blood donor, so that high-risk donors can confidentially exclude their blood from use for transfusions. 1 The first CSE system was designed in 1984 in the United States as an option for improving blood safety, 1 and similar systems have since been used in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data of the blood donor population can add to transfusion safety because it facilitates analysis of risk fac-30], but investigations in Norway found that HIV test seekers did not have particulars risks for acquiring an HIV infection [31]. In our study all HIV-positive donors between 2001 and 2005 and matched controls were questioned anonymously about donor motivation, knowledge about donation and infectious diseases and personal risk factors.…”
Section: Resultsmentioning
confidence: 97%